Five new species of Meta Koch, 1836 (Araneae: Tetragnathidae) from Gaoligong Mountains, China - Wang, Luyu; Zhou, Guchun; Irfan, Muhammad; Yang, Sufang; Peng, Xianjin (European Journal of Taxonomy, 2020)
Five new species of the genus Meta C.L. Koch, 1836 from the Gongligong Mountains, Yunnan are described: Meta hamata sp. nov. (♂♀), M. longlingensis sp. nov. (♂), M. tangi sp. nov. (♂♀), M. yani sp. nov. (♂♀) and M. yinae sp. nov. (♂♀). Detailed descriptions of somatic features and genitalic characters, photos of the body and genital organs, line drawings of the copulatory organs and distribution maps are provided.